Penerapan Yoga Prenatal dan Aromaterapi Lavender Untuk Meningkatkan Kualitas Tidur Ibu Pada Kehamilan Trimester Ketiga - Arini, Ketut Novia (Jurnal Abdi Mahosada, 2023)
In a woman's life cycle, there is a phase of pregnancy which is a time of great change. These changes are not only related to physical changes, but also psychological ones which are a consequence of the growth of the fetus in the womb. When entering the third trimester, more and more complaints are felt by the mother, which has a negative impact on the quality of sleep for pregnant women. Some physical changes in third-trimester pregnant women that can affect the quality of the mother's sleep are the presence of back pain due to the enlarged uterus due to the increased burden of the fetus it contains so that it affects the mother's posture and it is difficult to determine a comfortable sleeping position. This activity was carried out for 40 days starting with coordinating with the Head of the Puskesmas, outreach to the community until implementation. This activity involved six students, two supervisors and one yoga instructor with the target of 30 pregnant women. The application of prenatal yoga and lavender aromatherapy can significantly improve the quality of sleep for pregnant women.